The Analysis of Household Surveys : A Microeconometric Approach to Development Policy - Deaton, Angus (Washington, DC: World Bank, 2018)
Two decades after its original publication, The Analysis of Household Surveys is reissued with a new preface by its author, Sir Angus Deaton, recipient of the 2015 Nobel Prize in Economic Sciences. This classic work remains relevant to anyone with a serious interest in using household survey data to shed light on policy issues.